2014
DOI: 10.1111/jch.12455
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and the Development of Hypertension Over 5 Years in Black South Africans

Abstract: 2Alarming increases in the incidence of hypertension in many low-and middle-income countries are related to alcohol overuse. It is unclear whether alcohol overuse is a symptom of psychological distress. The authors assessed psychological distress in Africans and its relationship with a 5-year change in blood pressure (BP), independent of alcohol intake. The authors followed 107 Africans with optimal BP (≤120/80 mm Hg) (aged 35-75 years) over 5 years. Alcohol intake (self-report and serum c-glutamyl transferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…These rates coincide with previous findings in a study conducted by Kagee (2010) who found that the psychological distress experienced by South Africans living with hypertension and diabetes were similar. These findings were much lower than those reported in the South African nationally representative sample using a clinical interview for a diagnosis of a specific mental disorder, where 24.0 per cent of those individuals living with hypertension were found to have a mental disorder (Grimsrud et al, 2009) and in the study conducted with Black Africans where 23 per cent of respondents who developed hypertension reported psychological distress (Schutte et al, 2015). The prevalence of hypertension was similar among those who scored five or above on the AUDIT-C (indicating high risk alcohol use) and those who scored below five (low risk use).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…These rates coincide with previous findings in a study conducted by Kagee (2010) who found that the psychological distress experienced by South Africans living with hypertension and diabetes were similar. These findings were much lower than those reported in the South African nationally representative sample using a clinical interview for a diagnosis of a specific mental disorder, where 24.0 per cent of those individuals living with hypertension were found to have a mental disorder (Grimsrud et al, 2009) and in the study conducted with Black Africans where 23 per cent of respondents who developed hypertension reported psychological distress (Schutte et al, 2015). The prevalence of hypertension was similar among those who scored five or above on the AUDIT-C (indicating high risk alcohol use) and those who scored below five (low risk use).…”
Section: Discussioncontrasting
confidence: 65%
“…In a nationally representative study examining the relationship between mental health and the presence of hypertension in adults, results found that self-reported hypertension was associated with 12-month prevalence of anxiety disorders but not 12-month prevalence of depressive disorders (Grimsrud et al, 2009). A longitudinal study investigating the relationship between psychological distress, alcohol use and the onset of measured hypertension over a 5-year period among adult Black South Africans found that alcohol intake is associated with the onset of objectively measured hypertension, as did psychological distress independent of alcohol intake (Schutte et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study using the K6 observed higher rates of hypertension among individuals with psychological distress (39.2%) compared to those without (24.2%) [12]. Another longitudinal study of black South Africans, normotensive at baseline, showed that psychological distress was associated with twice the risk for future development of hypertension [24]. In a related cross-sectional study of hypertension across 9 countries (Armenia, Azerbaijan, Belarus, Georgia, Kazakhstan, Kyrgyzstan, Moldova, Russia and Ukraine), Footman et al [25] found a significant association between psychological distress (measured using the 12-item distress component of the Living Conditions, Lifestyles and Health Project) and hypertension with an odds ratio of 2.27 (95% CI 1.91-2.70).…”
Section: Discussionmentioning
confidence: 99%
“…More longitudinal studies of the frequency and risk factors of hypertension are needed in SSA to understand trends and clarify the relative contributions of the various environmental and genetic factors (as well as the gene‐environment interaction). Areas still unexplored include factors such as stress that may be becoming much more of a problem with urbanization in SSA …”
Section: The Importance Of Lifestyle or Behavioral And Lifestyles Facmentioning
confidence: 99%
“…Areas still unexplored include factors such as stress that may be becoming much more of a problem with urbanization in SSA. 24…”
Section: The Importance Of Lifestyle or Behavioral And Lifestyles Facmentioning
confidence: 99%